Group Level Interpretations of Probability: New Directions. (22nd October 2012) - Rowbottom, Darrell P.
Abstract In this article, I present some new group level interpretations of probability, and champion one in particular: a consensus‐based variant where group degrees of belief are construed as agreed upon betting quotients rather than shared personal degrees of belief. One notable feature of the account is that it allows us to treat consensus between experts on some matter as being on the union of their relevant background information. In the course of the discussion, I also introduce a novel distinction between intersubjective and interobjective interpretations of probability.